Recovery of a broken PICC migrated in cardiac chambersan endovascular approach - Giuseppe Sarti, MD; Pasquale Quassone, MD; Luca Tarotto, MD; Stefania Tamburrini, MD; Francesco Arienzo, MD; Gianpaolo Santini, MD (Radiology Case Reports, 2021)
Complications related to the placement of a peripherally inserted central catheter are a common phenomenon and they can lead to acute complications which must be treated in an emergency regime. The aim of this study was to describe cases in their most practical and technical aspect, especially in complicated conditions.This was a descriptive case report of a 64 years old female patient who presented with a fractured peripherally inserted central catheter, migrated into the right heart chambers and inferior vena cava, and how the team arranged for its recovery by endovascular technique, in a frail patient who could not undergo to open surgery.The procedure was completed without any complications. The use of the endovascular technique allows a recovery of the foreign body in a short time, essential for a life-saving procedure; the interventional radiological approach allows less invasiveness in fragile patients and shorter hospitalization times.